Inhibition of lipopolysaccharide-induced NF-κB maintains osteogenesis of dental pulp and periodontal ligament stem cells - Ferry SANDRA; Janti SUDIONO; Angliana CHOUW; Maria CELINNA; Nurrani Mustika DEWI; Melanie Sadono DJAMIL (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract Dental pulp stem cells (DPSCs) and periodontal ligament stem cells (PDLSCs) can differentiate into osteoblasts, indicating that both are potential candidates for bone tissue engineering. Osteogenesis is influenced by many environmental factors, one of which is lipopolysaccharide (LPS). LPS-induced NF-κB activity affects the osteogenic potencies of different types of MSCs differently. This study evaluated the effect of LPS-induced NF-κB activity and its inhibition in DPSCs and PDLSCs. DPSCs and PDLSCs were cultured in an osteogenic medium, pretreated with/without NF-κB inhibitor Bay 11-7082, and treated with/without LPS. Alizarin red staining was performed to assess bone nodule formation, which was observed under an inverted light microscope. NF-κB and alkaline phosphatase (ALP) activities were measured to examine the effect of Bay 11-7082 pretreatment and LPS supplementation on osteogenic differentiation of DPSCs and PDLSCs. LPS significantly induced NF-κB activity (p = 0.000) and reduced ALP activity (p = 0.000), which inhibited bone nodule formation in DPSCs and PDLSCs. Bay 11-7082 inhibited LPS-induced NF-κB activity, and partially maintained ALP activity and osteogenic potency of LPS-supplemented DPSCs and PDLSCs. Thus, inhibition of LPS-induced NF-κB activity can maintain the osteogenic potency of DPSCs and PDLSCs.